El arrecife coralino de Punta Cocles, costa Caribe de Costa Rica - Fernández García, Cindy (2004)
This paper describes the Punta Cocles reef (Limón, Costa Rica). Data were obtained by sampling nine transects along the coast and observations done by skin diving between September and November of 2002.This reef consist of 10.5 hectares, where 13 species of corals, 39 of macroalgae, two of seagrasses, two of zoantids, one anemone, one corallimorpharian, and one sponge were identified. Life coral coverage (16%), was higher than in other years (5% for 1985, and 13.2% for 1995), and death coral coverage was very low (0.2%). Macroalgae have the highest coverage (59%), particularly brown algae with a patchy distribution of Sargassum and Padina. Laurencia brongniartii (Rhodophyta) is added to the list of marine flora of Costa Rica. The Punta Cocles reef works as a refuge for organisms, because there are no towns or river mouths nearby, and because of the coast formation. The refuge character is enhanced by the environmental conscience of the people that live close to the reef and help to protect the environment.